Pengaruh EPS, PER, ROA, dan Firm SIze terhadap Return Saham pada perusahaan Food and Beverage yang terdaftar di BEI thaun 2020-2023 - Ninuk Kartika Sari (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to analyze the effect of Earning Per Share (EPS), Price Earning Ratio (PER), Return On Assets (ROA), and Firm Size on stock returns in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The research method used is quantitative with a purposive sampling approach, so that 15 companies are obtained as research samples. Secondary data was collected from the annual financial statements and stock prices of the companies concerned. Data analysis was carried out using multiple linear regression with the help of SPSS version 29 software. The results showed that partially, EPS, ROA, and Firm Size variables did not have a significant effect on stock returns, while PER had an effect but was not significant. Simultaneously, the four independent variables also have no significant effect on stock returns. Keywords : Earning Per Share, Price Earning Ratio, Return On Assets, Firm Size, Return Saham, Food and Beverage, Bursa Efek Indonesia